Dietary diversity and children anthropometric outcomes: A quantile regression analysis - Anjali Purushotham; Nitya Mittal; B. C. Aswini; K. B. Umesh; Stephan von Cramon-Taubadel; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
This study investigates the relationship between dietary diversity, a measure of diet quality, and health outcomes of young children. We examine this relationship not just at the mean, but also at different points of the conditional distributions of weight-for-age (WAZ) and height-for-age (HAZ) z-scores for children below six years of age, using quantile regression method. We construct five different dietary diversity measures using 14-day recall food consumption data collected in a primary survey conducted in in the rural-urban interface of Bangalore. Our results indicate no significant association between household dietary diversity and anthropometric outcomes of children below 6 years of age for any of the five measures.
Keywords: 330